The woodland gang and the indian cave - Schultz, Irene (Kalookan City : Addison-Wesley, 1991)
The Woodland Gang, Mrs. Tandy and Chief Hemster help search for a hidden cave on a friend's ranch.
Keywords: Mystery and detective stories; Orphans - Fiction